2019
DOI: 10.2139/ssrn.3363862
|View full text |Cite
|
Sign up to set email alerts
|

Policy News and Stock Market Volatility

Abstract: We thank the National Science Foundation and the University of Chicago Booth School of Business for financial support. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. At least one co-author has disclosed a financial relationship of potential relevance for this research. Further information is available online at http://www.nber.org/papers/w25720.ack NBER working papers are circulated for discussion and comment purposes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(88 citation statements)
references
References 71 publications
2
85
0
1
Order By: Relevance
“…Forward looking means the measure at least partly reflects anticipations of future developments rather than historical data. EPU is the Economic Policy Uncertainty index of Baker, Bloom and Davis (2016), and EMV is the Equity Market Volatility Tracker of Baker, Bloom, Davis and Kost (2019). Both are available in daily and monthly versions.…”
Section: Table 1: Measures Of Macro Uncertainty For the United Statesmentioning
confidence: 99%
“…Forward looking means the measure at least partly reflects anticipations of future developments rather than historical data. EPU is the Economic Policy Uncertainty index of Baker, Bloom and Davis (2016), and EMV is the Equity Market Volatility Tracker of Baker, Bloom, Davis and Kost (2019). Both are available in daily and monthly versions.…”
Section: Table 1: Measures Of Macro Uncertainty For the United Statesmentioning
confidence: 99%
“…Hence, we employ the baseline 5-factor VAR model where we replace the logarithm of the geopolitical risk index (LGPR) with alternative measures of uncertainty that have been suggested by the literature. In specific, we use the logarithm of 6 different uncertainty measures; that is the world uncertainty index (WUI) of Ahir et al (2019), the global economic policy uncertainty index (GEPU) of Davis (2016), the newspaper-based US economic policy uncertainty index (EPU) of Baker et al (2016), the newspaper-based equity market volatility tracker (EMV) of Baker et al (2019), the CBOE volatility index (VIX) as suggested by Bloom (2009), and the unobservable macroeconomic uncertainty index (MU) of Jurado et al (2015) (Figure 9). Furthermore, we employ a 6-factor VAR model where we add each different measure of uncertainty as an additional variable in our baseline VAR model (Figure 10).…”
Section: Robustnessmentioning
confidence: 99%
“…We also develop new indices for several policy categories, which we see as helpful in diagnosing the proximate sources of policy uncertainty and as potentially quite useful in analyzing policy uncertainty effects on industry-and firmlevel outcomes. Alexopoulos and Cohen (2015), Hlatshwayo and Saxegaard (2016), Azzimonti (2018), Caldara and Iacoviello (2018), Hassan et al (2019), Husted, Rogers and Sun (2019) and Baker et al (2019), among others, also use text analysis to quantify policy uncertainty and related concepts. Other approaches to quantification of policy uncertainty include Ito's (2016) survey-based measure for Japan, the country-level volatility of government consumption shocks in Fátas and Mihov (2013), the use of multivariate GARCH models in Grier and Perry (2000) and Vitek (2002), and time-varying measures of fiscal policy uncertainty derived from an estimated New Keynesian model in Fernandez-Villaverde et al (2015).…”
Section: Related Literaturementioning
confidence: 99%